Kilka uwag o teorii znaczenia Kazimierza Ajdukiewicza - Tomza, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The current discourse in the philosophy of law and philosophy of language is focused on one question – what is the proper meaning of the concept of meaning? The main problem in this reflections is a definition of a term ‘meaning’. Kazimierz Ajdukiewicz, the most renown Polish logician, which analyzed this problem, present the definition of ‘meaning’ as a proper understanding of the sense of the directives. Many current philosophers take this part of Ajdukiewicz’s work to demonstrate the cognitive part of the philosophy of law and especially the philosophy of language. In the Polish theory of law this issue is overlooked. In my opinion Ajdukiewicz was a creator of the philosophical concept ‘meaning’, and this article will consider the possibility that the idea of directive concept of ‘meaning’ and the conception of meaning belongs rather to the philosophy of language than constitutes the theory of logic.